IMPLEMENTATION OF INTEGRATED QUALITY MANAGEMENT PRIVATE CHARACTER EDUCATION IN IMPROVING DISCIPLINE OF STUDENTS - Odik Sodikin; Iim Wasliman; Sofyan Sauri; R. Sufyan Sauri (IJGIE (International Journal of Graduate of Islamic Education), 2022)
Education in Indonesia until now has not been able to answer moral inequality. This is because the education system that is schooling focuses on the transfer of knowledge and pays less attention to character education, limited hours of lessons, and the weak implementation of character education in educational institutions. Based on this, a breakthrough is needed to change the behavior of students, one of which is the Implementation of Integrated Quality Management in Islamic boarding schools, which can improve student discipline through training, habituation, and example. The purpose of the study was to determine and analyze the implementation of integrated management of noble character education in improving student discipline. The results of the study, that the quality of character education programs through good educational activities in dormitories or madrasas. The quality of kyai's leadership with charismatic leadership with a colligial collective management approach. Quality of the decision-making process with colligial collectives. Quality evaluation of character education with academic evaluation and parenting. The preserved values ​​of the pesantren are the five souls of the cottage, consisting of the values ​​of sincerity, simplicity, independence, ukhuwah Islamiyah and responsible freedom. The impact of character education is that the discipline character of the students is increased and the students are committed to the values ​​and rules of the pesantren. The Integrated Management-Based Character Education Model used, consists of inputs, processes, outputs and outcomes which are managed using an integrated management typical of Pesantren.